2018
DOI: 10.1007/s00894-018-3672-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigations into the intermolecular hydrogen-bonding interactions of N-(hydroxymethyl)acetamide dimers

Abstract: The structures of the N-(hydroxymethyl)acetamide (model molecule of ceramide) dimers have been fully optimized at B3LYP/6-311++G** level. The intermolecular hydrogen bonding interaction energies have been calculated using the B3LYP/6-311++G**, B3LYP/6-311++G(2df,2p), MP2(full)/6-311++G** and MP2(full)/6-311++G(2df,2p) methods, respectively. The results show that the O-H···O, N-H···O, O-H···N, and C-H···O hydrogen bonding interactions could exist in N-(hydroxymethyl)acetamide dimers, and the O-H···O, N-H···O, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…On the other hand, the H-bond donor, i.e., the hydrogen atom, shows a blue region that indicates a decrease of the electron density. These pictures are very similar to those found in previous EDS studies of hydrogen bonds, both intra- and intermolecular. , …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, the H-bond donor, i.e., the hydrogen atom, shows a blue region that indicates a decrease of the electron density. These pictures are very similar to those found in previous EDS studies of hydrogen bonds, both intra- and intermolecular. , …”
Section: Resultssupporting
confidence: 89%
“…These pictures are very similar to those found in previous EDS studies of hydrogen bonds, both intra- 40 and intermolecular. 41,42 Only the H atoms involved in the CH 3 •••HN interaction were optimized from the crystallographic coordinates. Natural bond orbital (NBO) analyses have been carried out to disclose the dominant orbital interactions involved in the studied hydrogen bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results clearly establish the key role of lipid chain length for the formation of a homogeneous lipid matrix. Intermolecular interactions between the components of SC lipid matrix include H-bonding at the head group level as well as van der Waals interactions at the chain level. Experimental and theoretical studies have shown the importance of H bonds in the structure of SC lipids. Extensive phase separations were observed in the CerNS16/FFA16/Chol mixture, a mixture for which the hydrophobic matching between the components is optimal. This finding suggests that interfacial intermolecular interactions are a driving factor of this phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that interfacial intermolecular interactions are a driving factor of this phase separation. The strength of Cer–Cer H-bonds has been estimated, from ab initio and density functional theory (DFT) methods, to vary between 20 and 62 kJ/mol; these should contribute to phase separations if they are more stable than those between ceramide and FFA and/or cholesterol. Actually, molecular dynamics simulations of CerNS24/FFA24/Chol mixtures showed that H-bonding between Cer–Cer pairs is dominating, if the H-bond involving water are not considered. In these studies, the lipid distribution was found to be homogeneous, except that molecular clusters involving about five molecules with a slight enrichment in CerNS were reported in one study .…”
Section: Resultsmentioning
confidence: 99%
“…However, high energy consumption of organic amine solvents is the main hindrance of large-scale applications for CO 2 capture due to high CO 2 reaction enthalpy with amines and large amounts of water vaporization. For example, the energy consumption of MEA aqueous solution regeneration for CO 2 capture from industrial flue gas was 3.50–4.20 GJ/ton CO 2 . Therefore, it has become a great challenge to develop novel solvents with low volatility, high absorption performance, and low energy consumption. , …”
Section: Introductionmentioning
confidence: 99%